THE PATH OF THE INDEPENDENT REPUBLIC OF UZBEKISTAN IN THE YEARS OF INDEPENDENCE AND TODAY'S PLANS AND ECONOMIC ANALYSIS (Marketing Journal, 2024)
The article describes the path taken by Uzbekistan, the essence of the concept of economic growth, its types, analysis of factors affecting the rate of economic growth, definitions given to economic growth, implementation of economic reforms its essence and necessity are analyzed. Considering the above, the current state of the country's growth was analyzed. Thus, the focus of this article is the importance of the factors of economic growth, that is, their role in the country's gross domestic product, and proposals for further improvement of the factors of economic growth.